Pengaruh Model Pembelajaran Kooperatif Tipe Scramble Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Sarana dan Prasarana Kelas XI OTKP di SMK Negeri 2 Tuban - Nur Oktafia Fadilawati; Novi Trisnawati (Universitas Negeri Surabaya, 2020)
The purpose of this research is to analyze the effect of the model cooperative type scramble on student learning outcomes the subject matter of facilities and infrastructure of class XI OTKP in SMK Negeri 2 Tuba. This type of research is a Quasi Eksperimental Design. The samples in this research used two calsses including XI OTKP 1 as an eksperiment of 34 students and XI OTKP 4 as a control of 34 students. Data analysis techniques used Homogeneity Test, Normality Test, and TTest (Hypothesis) and Gain Score Test with SPSS 22. The result of this study indicate that the completeness of student learning outcomes in the experiment class was declsred completed 97%, while in the control class was declared complete by 76,4%. The hypothesis test using the t test showed in the sig (2-tailed) table of 0,000 < 0,05 and tcount is 6,365 > ttable is 1,997%. Then Ha is accepted and H0 rejected, so it can be said that the learning model cooperative type scramble has a significant effect on improving student learning outcomes in class XI OTKP in SMK Negeri 2 Tuban.